Epistemological approaches in economics and education: transversal axes in science, technology, innovation and development - Soledispa-Cañarte, Betty Janeth; Baldovinos Leyva, Irma; Álvarez-Pincay, Dewis Edwin; Merchán-Ponce, Narda Paola (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Show a reflection on economic and educational epistemological approaches, offers different perspectives on the creation and application of knowledge to improve human life, so it is important to understand the different ways in which knowledge generation can be approached and its application of policies and strategies in key areas such as science, technology, Innovation and development. In a global context, epistemology plays a fundamental role in defining the theoretical and methodological frameworks that underpin research and decision-making in these areas, approaches ensure that development is equitable, resilient and sustainable, with a positive impact. The role of the university is fundamental for the stimulation of innovative capacity, especially in the educational system in Latin America; characterized by inequality and segmentation in access to knowledge, according to their educational capacity and income levels; Isolation of educational institutions from the social and economic realities of the local, regional and country level, and problems related to the quality and updating of knowledge, shortage of graduates in fundamental careers of socio-economic development, with initiatives and agents of change. Likewise, the praxis of the knowledge society explores the possibilities and limitations of different epistemological approaches, as well as their practical implications for the advancement of science, technology, innovation and development in the contemporary world.